2007
DOI: 10.1186/1471-2407-7-35
|View full text |Cite
|
Sign up to set email alerts
|

Growth regulation of simian and human AIDS-related non-Hodgkin's lymphoma cell lines by TGF-β1 and IL-6

Abstract: Background: AIDS-related non-Hodgkin's lymphoma (AIDS-NHL) is the second most frequent cancer associated with AIDS, and is a frequent cause of death in HIV-infected individuals. Experimental analysis of AIDS-NHL has been facilitated by the availability of an excellent animal model, i.e., simian Acquired Immunodeficiency Syndrome (SAIDS) in the rhesus macaque consequent to infection with simian immunodeficiency virus. A recent study of SAIDS-NHL demonstrated a lymphoma-derived cell line to be sensitive to the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
(74 reference statements)
2
8
0
Order By: Relevance
“…First, it has been demonstrated that many tumor cells express IL-6R, rendering them responsive to paracrine stimulation by IL-6 which the tumor clone itself generally fails to release [28]. Secondly, a further study has indicated that the sensitivity of immunoblastic HIV-related DLBCL to TGF-beta1-mediated growth inhibition may be overcome through the stimulation of proliferative and anti-apoptotic signals by IL-6, particularly the rapid activation of STAT3 [29]. Taken together, there is now preclinical data from HIV-related lymphoma as well as clinical data from both longitudinal observation and intervention with anti-IL-6 antibodies in PTLD to suggest an important role for IL-6 in both development and maintenance of malignant lymphocyte proliferation in a background of immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…First, it has been demonstrated that many tumor cells express IL-6R, rendering them responsive to paracrine stimulation by IL-6 which the tumor clone itself generally fails to release [28]. Secondly, a further study has indicated that the sensitivity of immunoblastic HIV-related DLBCL to TGF-beta1-mediated growth inhibition may be overcome through the stimulation of proliferative and anti-apoptotic signals by IL-6, particularly the rapid activation of STAT3 [29]. Taken together, there is now preclinical data from HIV-related lymphoma as well as clinical data from both longitudinal observation and intervention with anti-IL-6 antibodies in PTLD to suggest an important role for IL-6 in both development and maintenance of malignant lymphocyte proliferation in a background of immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune deficiency syndrome-derived diffuse large B-cell lymphoma cells are sensitive to growth inhibition by TGF-b; however, IL-6 production in these cells may overcome this inhibition by stimulating proliferative and antiapoptotic signals, particularly through the activation of STAT3. 80 Transgenic mouse studies suggest that IL-6 overexpression is involved in lymphoproliferative disorders, such as Castleman disease. 77 Patients may succumb to infections, or their disease may evolve to a more aggressive form.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…We recently characterized UMCL01-101 as immunoblastic AIDS-DLBCL (AIDS-IBL) based on expression of the EBV-encoded oncogenes LMP-1 and EBNA2 and the absence of detectable BCL-6. 46 Immunoblot analysis of total cellular protein demonstrated that 2F7 and UMCL01-101 cells express both PKCβ1 and PKCβ2. In contrast, BCBL1 cells lack PKCβ2 expression and express only PKCβ1 (Fig.…”
Section: Resultsmentioning
confidence: 96%